Gastric perforation in pediatrics patients: A case report with management (Indian Journal of Case Reports, 2024)
Gastric perforation is uncommon and life-threatening in infants and children. The mortality is up to 30–70%, and the most common cause is congenital gastric muscular wall defects. We reported the case of a 7-year-old boy from a rural locality of north India who presented in the emergency room with a chief complaint of fever for 15 days followed by abdominal pain associated with one episode of non-bilious vomiting and abdominal distention. The child had not passed stool for 3 days. On exploratory laparotomy, we found perforation of 0.5×0.5 cm at the anterior wall of the stomach near the pyloric region, more toward the lesser curvature of the stomach. The stomach, small intestine, and large intestine were loaded with pus flakes. Peritoneal lavage was done, and perforation was primarily repaired with Grahm patch omentopexy done. The patient was discharged on the sixth post-operative day without any complications. We concluded that gastric perforation in pediatric patients beyond the neonatal period may lead to fatal clinical outcomes, which causes a mortality rate of as high as 30%. Spontaneous great curvature of gastric wall perforation has the highest morbidity.